Phenological aspects of flowering and fruiting at the Ecological Station of Paulo de Faria-SP-Brazil - Stranghetti, V.; Ranga, N. Taroda [UNESP] (My University, 1997)
The present work was carried out at 'Estacao Ecologica de Paulo de Faria', north of the state of Sao Paulo, southeast of Brazil (19°55'-19°58'S and 49°31'-49°32'W). The flowering and fruiting phenology of trees, shrubs, and lianas species were observed from April 1993 to December 1995. The results were compaired with those surveyed at other forests from Sao Paulo state: Santa Genebra (Campinas). Serra do Japi (Jundiai) and lianas of Mata Atlantica. The majority of species of lianas flowered from January to April and trees and shrubs between September to December. The most intense frutification period occurred during May to August. Similarly to Santa Genebra, the flowering season at 'Estacao Ecologica de Paulo de Faria' started at the beginning of the wet season while frutification during the dryest period of the year. At Serra do Japi, the flowering and frutification occurred from the end of dry and beginning of the rainy season. Considering the liana at Mata Atlantica presented two peaks of flowering, while at 'Estacao Ecologica de Paulo de Faria' occurs only one. Regarding the fruiting phenology is similar for both area, most species producing fruits during the first semestre.
Keywords: Ecological Station of Paulo de Faria; Flowering; Fruiting; Liana; Shrub; Tree; flowering; fruiting; phenology; Brazil